1993
DOI: 10.1071/ea9930847
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cutting interval and winter dormancy on yield, persistence, nitrogen concentration, and root reserves of irrigated lucerne in the Queensland subtropics

Abstract: The use of fixed interval or growth stage (crown bud elongation) cutting management for lucerne was studied for cultivars with dormancy characteristics ranging from highly winter-active to winter-dormant. Fixed cutting intervals ranged from 3 to 8 weeks and were imposed on irrigated stands in a subtropical environment. Persistence, dry matter yield, weed yield, nitrogen (N) concentration and yield, and root reserves were measured over a 2-year period. For cultivars from all dormancy classes, persistence was hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 7 publications
3
16
1
1
Order By: Relevance
“…This difference in stand density between harvest regimes is consistent to the response of dry matter yield, since plots harvested at early bud also had low productivity (Rimi et al, 2010). Moreover, these results are similar to those of other studies where alfalfa harvested more frequently during the growing season had lower stand density (Sheaffer and Marten, 1990; Gramshaw et al, 1993; Ventroni et al, 2010). Kallenbach et al (2002) reported that harvesting four, five, or six times per year led to differences in plants m −2 during the first years of investigation, but these differences did not last more than 5 yr.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This difference in stand density between harvest regimes is consistent to the response of dry matter yield, since plots harvested at early bud also had low productivity (Rimi et al, 2010). Moreover, these results are similar to those of other studies where alfalfa harvested more frequently during the growing season had lower stand density (Sheaffer and Marten, 1990; Gramshaw et al, 1993; Ventroni et al, 2010). Kallenbach et al (2002) reported that harvesting four, five, or six times per year led to differences in plants m −2 during the first years of investigation, but these differences did not last more than 5 yr.…”
Section: Resultssupporting
confidence: 91%
“…2), which may be explained by declining intraspecific competition as the alfalfa stand aged (Hall et al, 2004). In November 2007, there was a stand density of 110 to 135 plants m −2 , which appear to be high absolute values in comparison to previous field experiments (Gramshaw et al, 1993; Kallenbach et al, 2002; Ventroni et al, 2010; Berti et al, 2012). The relatively high plant density observed here may be due to a high seeding rate used (i.e., 30 kg ha −1 ); however, the mortality dynamics were similar to those of Kallenbach et al (2002), who described an exponential reduction.…”
Section: Resultscontrasting
confidence: 51%
“…In this study, the diff erences between cutting frequencies were associated with a greater taproot mass in plants that were defoliated less frequently. In previous studies on forage legumes, frequent defoliation has been shown to reduce taproot biomass and organic reserves and subsequent yield (Gramshaw et al, 1993;Avice et al, 1997b;Teixeira et al, 2007). In fact, regrowth ability is highly dependent on the plant's capacity to mobilize C and N reserves stored in roots and stubble (Ta et al, 1990;Ourry et al, 1994;Volenec et al, 1996;Avice et al, 1997a).…”
Section: Discussionmentioning
confidence: 99%
“…However, total or partial removal of the photosynthetic area results in the mobilization of carbon and nitrogen reserves from roots to shoots (Avice et al ) generating an inversion of source and sink organs. After shoot removal, regrowth of the new shoot in alfalfa plants ( Medicago sativa ) is supported by non‐structural carbohydrates along with nitrogen compounds (such as proteins and amino acids) stored in the taproots (Gramshaw et al , Volenec et al , Avice et al , Dhont et al , , Pembleton et al ). During the regrowth period, these non‐structural carbohydrates are used to support respiration of the crown and taproots until photosynthesis is re‐established.…”
Section: Introductionmentioning
confidence: 99%